Investing in social care infrastructure and employment generation: A distributional analysis of the care economy in Turkey - Kijong Kim; çIpek çIlkkaracan; Tolga Kaya (Levy Economics Institute of Bard College, 2017)
This paper examines the aggregate and gender employment impact of expanding the early childhood care and preschool education (ECCPE) sector in Turkey and compares it to the expansion of the construction sector. The authors' methodology combines input-output analysis with a statistical microsimulation approach. Their findings suggest that the expansion of the ECCPE sector creates more jobs and does so in a more gender-equitable way than an expansion of the construction sector. In particular, it narrows the gender employment and earnings gaps, generates more decent jobs, and achieves greater short-run fiscal sustainability.
Keywords: I25; E17; R15; O23; 330; Early Childhood Care and Preschool Education; Employment; Gender Equality; Macroeconomic Impact; Microsimulation; Input-Output Analysis